The Pandemic of Disinformation - Francesco Pira (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: The continuing pandemic crisis represents a factor of profound destabilization, because it has exacerbated the phenomena already in place. In particular, social distancing, physical immobility have definitively shifted the construction of public discourse on the network, thus, giving rise to what is called "platform society", where it is the platforms that produce the social structures in which we live. Research Aim: The intervention intends to propose a reflection on how the processes of disinformation, accompanied by the crisis of authority of experts, propagated by a media system that increasingly feeds on information cascades and social propagation, have characterized the institutional communication at the time of the pandemic, its continued loss of authority, too often crushed between drifts induced by sub-politics and social dynamics. This narrative review is based on an analysis of the data collected from the empirical studies on the topic. Evidence-based Facts: The reduction of the spaces of personal freedom, the suspension of rights, have altered the relationship between citizens and institutions, further modifying and weakening the dimension of the public sphere. These dynamics have profoundly altered the circulation patterns of online information that have influenced the choices of users. Summary: The dynamics of proliferation of fake news thanks to the strength of their cross-mediality favor the entrenchment of polarized opinions that are consolidated thanks to a communicative construction centered on the feeling of fear.